Quantitative detection of Helicobacter pylori by real time PCR in drinking water - environmental and public health risk significance - Montero-Campos, Virginia; Arias-Cordero, Shirley; Valdés-Rodríguez, Benedicto; Jarquín-Cordero, Monserrat (Instituto Tecnológico de Costa Rica, 2017)
Conferencia: Quantitative detection of Helicobacter pylori by real time PCR in drinking water - environmental and public health risk significance, presentada por Virginia Montero-Campos, Shirley Arias-Cordero, Benedicto Valdés-Rodríguez, Monserrat Jarquín-Cordero, en el año 2017
Conferencia. Instituto Tecnológico de Costa Rica. Escuela de Biología. Centro de Investigación en Biotecnología, 2017
Keywords: Detección -- Helicobacter pylori; Tiempo real; Agua potable; Riesgos ambientales; Salud pública; Desarrollo sostenible; Epidemiología - Microbiología; Cáncer gástrico; Detection -- Helicobacter pylori; Real time; Drinking water; Environmental risks; Public health; Sustainable development; Epidemiology - Microbiology; Gastric cancer; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering; Research Subject Categories::PHARMACY::Toxicology; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas